THE CONCEPT «MOUNTAIN » IN THE LANGUAGE CONSCIOUSNESS OF THE KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article notes that the Kyrgyz language is a historical language that reflectsthe consciousness, worldview and culture of the nation. It is believed that the character, lifestyleand culture of the Kyrgyz people are formed under the influence of the surrounding geographicenvironment, climate and are reflected in linguistic information. Linguistic information, whichexpresses the consciousness and thoughts of a nation, is expressed in a simple and concise form interms of the structure of each regular expression, proverbs, aphorisms, literary texts.They contain deep philosophical thoughts that inspire. On the basis of scientific views, it wasestablished that space has a special effect on people’s lives and that the material sources of theirdevelopment are expressed through language. The essence of the “mountainous” segment, whichforms the basis of the “space” category in the Kyrgyz linguistic image of the world, is analyzed,as well as its reflection in the linguistic consciousness of the Kyrgyz people. In linguistics, formedon the basis of the Kyrgyz national worldview, the “mountain” sign is considered as a concept inthe Kyrgyz linguistic image of the world. The expression of national norms of behavior throughlinguistic information is considered in relation to the image of the mountain. The word «mountain»refers to patience, strength, intelligence, knowledge, goals, time, season, and so on. It was foundto be used as a linguistic symbol, a metaphor that forms a similar relationship with words. Thefacts have shown that the word «mountain» is widely used as a linguistic symbol in phraseology,paremia and literary texts.
Keywords: picture of the world, linguistic picture of the world, spatial picture of the world, category «space», concept, concept «mountain», symbol, metaphor, image, background knowledge, etc.